Effect of administrative skills on the secretarial profession in tertiary institutions in Ekiti State - Hammed, Abosede Fisayo; Olawale, Olusanya Joseph (Journal of Professional Secretaries and Office Administrators, 2022)
Effect of administrative skills on the secretarial profession in tertiary institutions in Ekiti State